2023
DOI: 10.3389/fendo.2023.1115890
|View full text |Cite
|
Sign up to set email alerts
|

Integrative network-based analysis on multiple Gene Expression Omnibus datasets identifies novel immune molecular markers implicated in non-alcoholic steatohepatitis

Abstract: IntroductionNon-alcoholic steatohepatitis (NASH), an advanced subtype of non-alcoholic fatty liver disease (NAFLD), has becoming the most important aetiology for end-stage liver disease, such as cirrhosis and hepatocellular carcinoma. This study were designed to explore novel genes associated with NASH.MethodsHere, five independent Gene Expression Omnibus (GEO) datasets were combined into a single cohort and analyzed using network biology approaches.Results11 modules identified by weighted gene co-expression n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…The model was compared with previously published NASH-related biomarkers. In total, 43 NASH diagnostic genes were identified in nine previous studies [ 24 32 ]. Notably, FeRS also exhibited good predictive performance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The model was compared with previously published NASH-related biomarkers. In total, 43 NASH diagnostic genes were identified in nine previous studies [ 24 32 ]. Notably, FeRS also exhibited good predictive performance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Transcription factors such as SPI1, ETS1, and CEBPA have been identified as promising targets for the prevention and treatment of NASH ( 64 ). These transcription factors are integral components of a complex regulatory network involving TF-miRNA-mRNA interactions, highlighting the sophisticated molecular interplay underlying NASH pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that CEBPA/B is key comorbidities transcription factor for NASH and PBC, which is consistent with other studies. Zhang et al [19]found that CEBPA is one of the key transcription factors in NASH, and increases with the progression of NASH. Frietze et al [20]found that CEBPB participates in autophagy activated by DDX58, alleviates in ammation and apoptosis caused by lipid toxicity, and delays the progression of NASH.…”
Section: Discussionmentioning
confidence: 99%